Worker Protection Standard: Requirements for Agricultural Employers of Workers and Handlers - Frederick M. Fishel (EDIS)
Safety is a high concern for agricultural employers whose workers deal with hazardous materials, such as pesticides. In 1992, the US Environmental Protection Agency (EPA) issued the Worker Protection Standard for Agricultural Pesticides (WPS), a regulation that requires agricultural employers to take steps to reduce pesticide-related risks for their workers and handlers. This five-page document describes the responsibilities of employers who must adhere to the WPS. Written by Frederick M. Fishel and published by the UF/IFAS Agronomy Department, January 2018. http://edis.ifas.ufl.edu/ag417